Computational System Level Approaches for Discerning Reciprocal Regulation of IL10 and IL12 in Leishmaniasis - Khandibharad, Shweta; Singh, Shailza (Frontiers in Genetics, 2022)
IL12 and IL10 are one of the major cytokines which control the fate of Leishmaniasis. This paper presents two models Healthy state and Diseased state which shows how secretion of IL12 is responsible for parasite elimination and IL10 can jeopardize the parasite elimination and promote its survival. Epigenetic modification in the host IL12 and IL10 promoter can decide the fate of parasites. It was observed that reciprocal relationship exists between IL12 and IL10 and that is majorly controlled by a transcription factor NFAT5 from Rel family of transcription factors. By targeting this transcription factor at the cellular level, it might be possible to modulate the release of powerful pro-inflammatory cytokines, thereby reducing parasite survival. The mathematical models developed here serves as a step towards finding a key component that can pave a way for therapeutic investigation.